The effect of X-ray irradiation on ultrasound attenuation and velocity in LiF single crystals - Petchenko, O.M.; Petchenko, G.O.; Boiko, S.M.; Litvinenko, A.S. (Functional Materials, 2019)
Using the pulsed method at a frequency of 7,5 MHz, the dependences of dislocation absorption and ultrasound velocity in LiF single crystals with residual deformation ε = 0,65 % at T = 300 K in the dose range of 0-1057 R were investigated. It has been established that, under conditions of crystals' irradiation with X-rays, the concentration of radiation centers fixing easily mobile dislocations significantly increases. As a result of limiting these dislocations' number, the attenuation of ultrasound decreases sharply, and its propagation velocity in the sample increases.